Influence of cone-beam computed tomography image artifacts on the determination of dental arch measurements - Gamba, Thiago O.; Oliveira, Matheus L. [UNESP]; Flores, Isadora L.; Cruz, Adriana D.; Almeida, Solange M.; Haiter-Neto, Francisco; Lopes, Sergio L. P. C. [UNESP] (E H Angle Education Research Foundation, Inc, 2014)
Objective: To compare dental plaster model (DPM) and cone-beam computed tomography (CBCT) in the measurement of the dental arches, and investigate whether CBCT image artifacts compromise the reliability of such measurements.Materials and Methods: Twenty patients were divided into two groups based on the presence or absence of metallic restorations in the posterior teeth. Both dental arches of the patients were scanned with the CBCT unit i-CAT, and DPMs were obtained. Two examiners obtained eight arch measurements on the CBCT images and DPMs and repeated this procedure 15 days later. The arch measurements of each patient group were compared separately by the Wilcoxon rank sum (Mann-Whitney U) test, with a significance level of 5% (alpha = .05). Intraclass correlation measured the level of intraobserver agreement.Results: Patients with healthy teeth showed no significant difference between all DPM and CBCT arch measurements (P > .05). Patients with metallic restoration showed significant difference between DPM and CBCT for the majority of the arch measurements (P > .05). The two examiners showed excellent intraobserver agreement for both measuring methods with intraclass correlation coefficient higher than 0.95.Conclusion: CBCT provided the same accuracy as DPM in the measurement of the dental arches, and was negatively influenced by the presence of image artifacts.
Keywords: Anatomic models; Cone-beam computed tomography; Orthodontics